Potensi Green budgeting dalam Meningkatkan Efisiensi Pengeluaran Publik untuk Mewujudkan Pembangunan Berkelanjutan di Indonesia - Siti Mutmainah; Slamet Wijiono; Muhammad Ryan Romadhon (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Climate change is a global challenge that affects various aspects of life, including economic development. The concept of green budgeting has emerged as an important strategy to ensure the efficiency of public spending while supporting sustainable development in Indonesia. This research analyzes the potential of green budgeting to enhance the efficiency of environmental budget management, focusing on public fiscal policies that align with sustainability. By implementing mechanisms such as climate-based budgeting (CBT), the government can increase the budget for programs aimed at mitigating and adapting to the impacts of climate change, but also faces structural challenges such as a lack of human resources and the absence of a comprehensive oversight system. This study adopts a qualitative approach to identify the relationship between public expenditure efficiency and the implementation of green budgeting in development policy, using literature review methods. Research results show that the distribution of green budgets in the state budget (APBN) is still limited, indicating a potential inefficiency in fund allocation. Therefore, it is necessary to enhance institutional capacity, integrate monitoring systems, and commit to implementing fiscal policies that consider the environment by both the central and local governments.